The Thyrotropin Receptor Hinge Region as a Surrogate Ligand: Identification of Loci Contributing to the Coupling of Thyrotropin Binding and Receptor Activation - Chen, Chun-Rong (Endocrine Society, 2012)
The TSH receptor (TSHR) hinge region, the least well understood component, bridges the leucine-rich repeat and transmembrane domains. We report data on clusters of hinge charged residues the mutation of which to Ala is compatible with cell surface expression and normal, or near normal, TSH binding affinity yet with a relative reduction in receptor activation. Mutation to Ala of E409 at the junction with the transmembrane domain was the most potent in uncoupling TSH binding and signal transduction (∼22-fold less sensitive than the wild-type TSHR) and was unique among the residues studied in reducing both the amplitude and the sensitivity of the ligand-induced signal. Unexpectedly, a dual E409A/D410A mutation partially corrected the major suppressive effect of TSHR-E409A. The combined Ala substitution of a cluster of positively charged hinge residues (K287, K290, K291, R293; termed “K3R1”) synergistically reduced sensitivity to TSH stimulation approximately 21-fold without altering the TSH binding affinity. Simultaneous Ala substitutions of a cluster of acidic hinge residues D392, E394, and D395 (termed “DE392-5A”) partially uncoupled TSH binding from signal transduction (4.4-fold reduction in sensitivity), less than for E409A and K3R1A. Remarkably, the combination of the K3R1A and DE392-5A mutations was not additive but ameliorated the major uncoupling effect of K3R1A. This lack of additivity suggests that these two clusters contribute to a common signaling pathway. In summary, we identify several TSHR hinge residues involved in signal transmission. Our data support the concept that the hinge regions of the TSHR (and other glycoprotein hormone receptors) act as surrogate ligands for receptor activation.